Laboratory-based surveillance of COVID-19 in the Greater Helsinki area, Finland, February–June 2020. (March 2021) - Jarva, H.; Lappalainen, M.; Luomala, O.; Jokela, P.; Jääskeläinen, A.E.; Jääskeläinen, A.J.; Kallio-Kokko, H.; Kekäläinen, E.; Mannonen, L.; Soini, H.; Suuronen, S.; Toivonen, A.; et al.
Highlights: Female subjects seek SARS-CoV-2 testing more frequently than male subjects. The positivity rate for SARS-CoV-2 was significantly higher in tested men in Finland. The proportion of SARS-CoV-2-positive young adults seemed to increase in late May. Abstract: Objectives: The aim was to characterise age- and sex-specific severe acute respiratory syndrome coronavirus disease-2 (SARS-CoV-2) RT-PCR sampling frequency and positivity rate in Greater Helsinki area in Finland during February–June 2020. We also describe the laboratory capacity building for these diagnostics. Methods: Laboratory registry data for altogether 80, 791 specimens from 70, 517 individuals was analysed. The data included the date of sampling, sex, age and the SARS-CoV-2 RT-PCR test result on specimens collected between 1 February and 15 June 2020. Results: Altogether, 4057/80, 791 (5.0%) of the specimens were positive and 3915/70, 517 (5.6%) of the individuals were found positive. In all, 37% of specimens were from male and 67% from female subjects. While the number of positive cases was similar in male and female subjects, the positivity rate was significantly higher in male subjects: 7.5% of male and 4.4% of female subjects tested positive. The highest incidence/100, 000 was observed in those aged ≥80 years. The proportion of young adults in positive cases increased in late May 2020. Large dips in testing frequency were observed during every weekend and also during public holidays. Conclusions: Our data suggest that men pursue SARS-CoV-2 testing less frequently than women. Consequently, a subset of coronavirus disease-2019 infections in men may have gone undetected. People sought testing less frequently on weekends and public holidays, and this may also lead to missing of positive cases. The proportion of young adults in positive cases increased towards the end of the study period, which may suggest their returning back to social behaviour with an increased risk of infection.